Digital Implementation of DSVPWM Control for EV fed through Impedance Source Inverter - Ananda Kumar Akkarapaka; Dheerendra Sing (Institute of Advanced Engineering and Science, 2015)
In this paper, a new space vector modulation technique is proposed for speedcontrol of Induction Motor using Z-source inverter powered by a low voltage DCsource. The zero states of conventional space vector modulation is used for boosting the DC link voltage to the required level. The proposed SVM techniqueestimates the required shoot through period of the Z-source inverter to maintainthe DClink voltage constant at the desired level through capacitor voltage control.A 32 bit DSP (TMS320F28335) is used to implement the proposed space vectormodulation method. The power structure and the modulation technique is wellsuited for electric vehicle application.